(untitled) (Research, Society and Development, 2020)
Introduction: Diabetes mellitus (DM) is characterized as a chronic non-communicable disease (NCD) in which the body does not produce or cannot effectively use a hormone called insulin , which is responsible for controlling the amount of glucose in the bloodstream, as a method to avoid complications caused by this comorbidity the federal government has implemented family health strategies, in 2020, the ESF had to make changes in their care to the population due to the pandemic caused by Sar-Cov-2. Objective: the objective of this study was to identify which influence the pandemic caused by Covid-19 caused the glycemic indices of patients with DM. Methodology: this is a descriptive study of a quantitative qualitative nature, developed in a Family Health Strategy located in the Northern Zone of the State of Rio de Janeiro conducted with 10 nurses crowded in the unit performing a search of medical records and glycated hemoglobin tests to identify the alterations caused by the pandemic, Bardin methodology was used for content analysis. Result and Discussion: 213 medical records were analyzed that were part of the inclusion criteria, and all presented alterations in glycemic indices. Conclusion: Primary health care and its multidisciplinary teams are extremely important for the prevention of diseases and promotion of diseases, this was evident in the care that the teams had to treat respiratory symptoms and as health professionals we must always put the community good in front of economic values, value and respect epidemiological statistics.